ANALISIS TINGKAT HUNIAN DAN PENDAPATAN HOTEL DI KABUPATEN JEMBER SELAMA BULAN BERKUNJUNG KE JEMBER (BBJ) - Susanto, Andri Mardi; Susanti, Indria Yuli; Neviyani, Neviyani (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2015)
Visits to Jember Month (BBJ) is an annual event held by the Government of Jember, creating a form of tourism in the form of entertainment activities such as sports, arts, culture, and science. This study aims to analyze the occupancy rate and the number of traveller spositive effect on hotel revenues during a visit to Jember (BBJ) in Jember. The sample in this study is that there are hotels in Jember City District as much as 31 hotels. Based on calculations SPSS version 16.0 for windows found results positive effect on the occupancy rate of income in Jember. While the number of tourists no significant effect on hotel revenues. Keywords: occupancy rate, tourist, revenue